The Mycobacterium smegmatis bd -II terminal oxidase employs a carboxylate shift mechanism - Terezia Kovalova; Mateusz Janczak; Ana P. Gamiz-Hernandez; Daniel Lundin; Soni Sharma; Johanna Vilhjálmsdóttir; Dan Sjöstrand; Ville R. I. Kaila; Martin Högbom; Pia Ädelroth (Proceedings of the National Academy of Sciences, 2026)
Cytochrome bd is a terminal oxidase expressed under low oxygen conditions and central for the survival of many pathogens. Here, we characterize the cyt bd -II from Mycobacterium smegmatis , a member of a hitherto uncharacterized evolutionary group (qOR-2) of bd oxidases, by combining biochemical studies with cryo-electron microscopy (cryo-EM), and multiscale simulations. Overexpressing the appCB operon in its native host led to production of a highly active bd -II ( k obs = 30 e − s −1 ) that together with a high-resolution (2.8 Å) cryo-EM structure and multiscale simulations reveal unique proton pathways and oxygen channels responsible for its function. We propose that a pH-dependent molecular switch, involving coordination changes of heme d and surrounding bulky residues regulate substrate access into the active site. Taken together, our findings provide detailed mechanistic insight of qOR-2 type bd oxidases, and a basis for understanding the evolution of the superfamily.